La importancia de la planificación financiera personal - Estefani Yuliet Maldonado Cáceres; Yulieth Katerin Melo Martínez; Blanca Mery Rolon Rodríguez (Mundo Fesc)
Personal financial planning is important and crucial for maintaining control over income and expenses, creating an emergency fund, achieving financial goals, optimizing resources, reducing debt, encouraging investments, and improving financial literacy. This provides stability, security, and facilitates the achievement of short- and long-term financial goals. For this article, sources such as Google Scholar and Scielo were reviewed using a documentary design. This research discusses how to carry out successful personal financial planning, covering topics such as investing, which helps maintain the value of money against inflation and generate additional income, a tool for perseverance and increasing wealth. Savings, which allows for financial security and achieving goals. Financial management, which provides control over income and expenses and aids in strategic decisions. Debt management allows us to minimize costs and maintain a good credit score. All of these aspects are important for maintaining sound personal finances, free from errors that could be detrimental to one's income, and for maintaining a healthy financial life and preparing for emergencies. Results: The research also addresses financial security, which is achieved with a stable income, spending less than you earn, avoiding debt, and setting financial goals. Controlling your finances, supporting decisions, and measuring financial performance guides you toward the efficient use of resources, protecting your assets, and ensuring the economic viability to achieve your financial goals and live a more peaceful and financially secure life.